Information systems in district development planning: a case study of Yilo Krobo District, Ghana - Nakaanda, Brian Nyama (2011)
A Thesis submitted to the School of Graduate Studies, University of Science and Technology, Kumasi in partial fulfillment of the requirements for the Degree of Master of Science in Development Planning and Management.